Mapping Publication Trends dalam Pendidikan STEM dari Database Scopus: Analisis Bibliometrik - Bagus Pratomo Nusantoro; Paidi Hw; Kintan Limiansi (SAP (Susunan Artikel Pendidikan), 2026)
The rapid growth of publications in STEM education highlights the need for a systematic mapping to better understand the direction of research development. This study aims to map publication trends in STEM education research indexed in the Scopus database through bibliometric analysis to identify research development, dominant themes, and future directions. The study employed a descriptive quantitative approach using bibliometric methods. Data were collected from Scopus through PRISMA stages consisting of identification, screening, eligibility, and inclusion, resulting in 377 final articles from 798 initial records, which were analyzed using Biblioshiny and VOSviewer. The findings show that STEM education publications have increased significantly, particularly since 2015, with an annual growth rate of 22.88%. The United States was the leading contributor, followed by China and Australia, while international collaboration indicates the strengthening role of Asia-Pacific countries. Keyword co-occurrence analysis reveals that STEM education research is mainly focused on STEM integration in learning, student learning outcomes, critical thinking and assessment, and the use of technology in teaching and learning..